EXPLORING ISLAMIC EDUCATION LEARNING BASED ON BOARDING SCHOOL IN BUILDING STUDENTS ETHIC AT ISLAMIC JUNIOR SCHOOL AL-ISLAH, MAROS - Ahsanuddin Ahsanuddin (Universitas Islam Negeri Alauddin Makassar, 2022)
This research is qualitative research with pedagogic, sociological, and theological approaches. The research location was at the IT Al-Ishlah Maros Middle School, as informants in this study the chairman of the foundation, school principal, teachers, hostel supervisors, students, and parents of students. Based on the findings of the study, Islamic Boarding School-based learning at SMP IT Al-Ishlah is divided into two formal and informal. Then the role of PAI learning is fostering student morals, among these roles are fostering morals in loving the environment, making students have disciplined morals, getting used to behaving politely, increasing religious understanding, getting used to independent behavior, and making students with honest character.